Impaired SUMOylation of nuclear receptor LRH-1 promotes nonalcoholic fatty liver disease - Stein, Sokrates; Lemos, Vera; Xu, Pan; Demagny, Hadrien; Wang, Xu; Ryu, Dongryeol; Jimenez, Veronica; Bosch, Fatima; Lüscher, Thomas F.; Oosterveer, Maaike H.; Schoonjans, Kristina (The Journal of Clinical Investigation, 2017)
Hepatic steatosis is caused by metabolic imbalances that could be explained in part by an increase in de novo lipogenesis that results from increased sterol element binding protein 1 (SREBP-1) activity. The nuclear receptor liver receptor homolog 1 (LRH-1) is an important regulator of intermediary metabolism in the liver, but its role in regulating lipogenesis is not well understood. Here, we have assessed the contribution of LRH-1 SUMOylation to the development of nonalcoholic fatty liver disease (NAFLD). Mice expressing a SUMOylation-defective mutant of LRH-1 (LRH-1 K289R mice) developed NAFLD and early signs of nonalcoholic steatohepatitis (NASH) when challenged with a lipogenic, high-fat, high-sucrose diet. Moreover, we observed that the LRH-1 K289R mutation induced the expression of oxysterol binding protein-like 3 (OSBPL3), enhanced SREBP-1 processing, and promoted de novo lipogenesis. Mechanistically, we demonstrated that ectopic expression of OSBPL3 facilitates SREBP-1 processing in WT mice, while silencing hepatic Osbpl3 reverses the lipogenic phenotype of LRH-1 K289R mice. These findings suggest that compromised SUMOylation of LRH-1 promotes the development of NAFLD under lipogenic conditions through regulation of OSBPL3.